2023
DOI: 10.1029/2022jd037817
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Atmospheric Carbonyl Sulfide (TransCom‐COS; Part One): Evaluating the Impact of Transport and Emissions on Tropospheric Variability Using Ground‐Based and Aircraft Data

Abstract: We present a comparison of atmospheric transport model simulations for carbonyl sulfide (COS), within the framework of the ongoing atmospheric tracer transport model intercomparison project "TransCom". Seven atmospheric transport models participated in the inter-comparison experiment and provided simulations of COS mixing ratios in the troposphere over a 9-year period (2010-2018), using prescribed state-of-the-art surface fluxes for various components of the atmospheric COS budget: biospheric sink, oceanic sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 117 publications
(315 reference statements)
1
28
0
Order By: Relevance
“…The ATMs then simulated the atmospheric COS concentration (3D) following the transport of COS surface fluxes. For a comparison to the results with the optimized fluxes, we also present results from the control scenario described in part I (Remaud et al., 2023a). Relying on the linearity of the atmospheric transport, each flux of the control scenario was transported separately by all participating models, after which the contributions were added.…”
Section: Transport Model Cos Fluxes and Measurements And Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The ATMs then simulated the atmospheric COS concentration (3D) following the transport of COS surface fluxes. For a comparison to the results with the optimized fluxes, we also present results from the control scenario described in part I (Remaud et al., 2023a). Relying on the linearity of the atmospheric transport, each flux of the control scenario was transported separately by all participating models, after which the contributions were added.…”
Section: Transport Model Cos Fluxes and Measurements And Protocolmentioning
confidence: 99%
“…TM3 did not provide 3D model output and is assumed to be in the strong mixing group, because the vertical transport parameterization is similar to TM5. The impact of the vertical mixing on the seasonal cycle is known as the seasonal rectifier effect (Denning et al, 1995) and is shown in the case of COS on Figure 4 in Remaud et al (2023a).…”
Section: Participating Models and Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a major challenge of using COS as a global‐scale GPP proxy is the imbalance of the global COS budget, as recently highlighted in the intercomparison of atmospheric COS transport models conducted by Remaud et al. (2023). A previous inversion study by Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a major challenge of using COS as a global-scale GPP proxy is the imbalance of the global COS budget, as recently highlighted in the intercomparison of atmospheric COS transport models conducted by Remaud et al (2023). A previous inversion study by Ma et al (2021) has suggested the likely presence of a missing COS source in the tropics, and an underestimated COS sink in northern high latitudes.…”
mentioning
confidence: 99%